Co-pyrolysis of Pyridine and Pyrrole as Nitrogenous Compounds Model of Coal - Zhao, Qinxin; Wang, Xuebin; Tan, Houzhang; Si, Jipeng; Niu, Yanqing; Xu, Tongmo (Asian Journal of Chemistry, 2010)
Nitrogen in coal mainly exists in the form of pyrrolic nitrogen and pyridinic nitrogen, in this work, pyridine and pyrrole has been chosen as the nitrogenous model compound to investigate the transformation of nitrogen in coal during pyrolysis and combustion. The pyrolysis of mixture of pyridine and pyrrole is performed at 873-1473 K in a flow reactor and the products are analyzed by FTIR combined with GC. Results show that the thermal stabilization of pyridine is better than pyrrole and pyridine produces more H2 but less HCN. HCN yield of co-pyrolysis is lower than the separate pyrolysis of both pyridine and pyrrole. Co-pyrolysis releases more HCN with the increase of pyridine content at 1373 K, in contrast to 1073 K. The change of H2 is similar to HCN as the temperature and mixing ratio change and CH4 is detected with low yield.